Pengembangan Karakter Berbasis Nilai Religius Di SMK Teknologi Komputer MBM Rawalo Banyumas - Sumiarti Sumiarti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This research is based on the researcher's interest to know more deeply and then to describe the implementation of character education in a high school / vocational school. As one of the SMK